2009
DOI: 10.1007/978-3-642-03655-2_11
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Human and Avatar Facial Expressions

Abstract: This paper investigates the impact of contradictory emotional content on people's ability to identify the emotion expressed on avatar faces as compared to human faces. Participants saw emotional faces (human or avatar) coupled with emotional texts. The face and text could either display the same or different emotions. Participants were asked to identify the emotion on the face and in the text. While they correctly identified the emotion on human faces more often than on avatar faces, this difference was mostly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
3
8
0
Order By: Relevance
“…They found that neutral expressions were more easily recognized on a human face than on an avatar. They also found that for the avatar faces, sadness was confused with the neutral face, supporting similar findings by Noël et al (2009).…”
Section: Emotional Communicationsupporting
confidence: 69%
See 2 more Smart Citations
“…They found that neutral expressions were more easily recognized on a human face than on an avatar. They also found that for the avatar faces, sadness was confused with the neutral face, supporting similar findings by Noël et al (2009).…”
Section: Emotional Communicationsupporting
confidence: 69%
“…They conclude that facial expressions cannot be considered in isolation. More recently, Noël et al (2009) described a study comparing emotions depicted in avatar facial expressions and short captions presented in speech bubbles. Five emotions were considered (anger, happiness, neutral, sadness and surprise) and congruent and incongruent presentations evaluated.…”
Section: Emotional Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…a sad emotion for an angry statement) were still judged as having a less appropriate emotional expression but were not judged any less trustworthy, less convincing, or less sincere than the congruent case. There were no significant differences between the judgment of avatar faces and photorealistic faces [Noël et al 2009]. …”
Section: Usability Solutionsmentioning
confidence: 99%
“…Carroll and Russell (1996) asserted that contextual information is crucial to identify or infer emotional states. To illustrate, a different emotion is attached to a crying avatar in Second Life when the accompanying chat message explains that the individual whom the avatar represents has either lost his job or got promoted (Noël, Dumoulin & Lindgaard, 2009). It thus seems plausible that emotion recognition is sensitive to the meaning of the scene in which a virtual human character appears.…”
Section: Introductionmentioning
confidence: 99%